La sexualidad en los jóvenes de sectores marginales. Un informe de avance (2004)
ABSTRACT: The sexuality in the young people of marginal sectors. The problem is the sexuality of the adolescents in a poverty world and inequidad. This study must like general mission describe to the crude sexual products of the misery and the myths that they poison to marginal youth. It is an attempt to portray those adolescents who know sex in the school the underworld which they hide cords of extreme poverty of the Medellín of today. The mentioned results correspond to concrete realities product of an opinion poll in some marginal districts of the city of Medellín.